Comparison of functional and morphological estimates of vascular age - Sigl, Martin; Winter, Laura; Schumacher, Gerhard; Helmke, Stefanie Christina; Shchetynska-Marinova, Tetyana; Amendt, Klaus; Dürschmied, Daniel; Hohneck, Anna (In vivo, 2023)
Background/Aim: Vascular age (VA) is an emerging metric in preventive cardiovascular (CV) medicine. VA can be derived from morphological parameters such as carotid intima-media thickness (CIMT), or functional parameters such as pulse wave analysis (PWA), which celebrates its 100th birthday. This study aimed to investigate whether the results of both approaches are comparable. Patients and Methods: On the occasion of the double 100th anniversary of PWA and the Mannheim Clinic, 100 volunteers underwent a) bilateral CIMT assessment using high-resolution ultrasound and b) oscillometric PWA at the brachial forearm site. The respective VAs were calculated using previously published equations. Results: Median age of the participants was 53.6 years (range=39.8-62.6 years), and 56% were female. Median CIMT was 632.5 μm (range=548.8-730.0 μm). Median PWA-derived VA was 55.3 years (36.5-70.5 years). Different values were obtained for CIMT-derived VA, depending on the reference cohort used as calculation basis, ranging from median 43.7 (26.2-59.5 years) to median 64.0 years (43.5-82.1 years). In 46% of the participants divergent VAs were found, that is, the calculated age was higher according to one method and lower according to the other. Correlation analysis revealed a strong dependence of VA (both PWA- and CIMT-derived) and chronological age, as well as an increase in CV risk factors and the detection of plaques with age. Conclusion: Different approaches for estimating VA are not comparable and often produce contradictory results. The current methods and their validity must be critically assessed if they are not standardized.
Online veröffentlicht: 31. August 2023
Gesehen am 08.10.2024